EFISIENSI PEMASARAN JAGUNG DI KELURAHAN KALAMPANGAN KECAMATAN SABANGAU KOTA PALANGKA RAYA - Novica Sari Br Purba; H. Ahmad Zaki Yamani; Pordamantra, Pordamantra (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
The aim of this research is to analyze marketing channel, marketing institution, marketing function, marketing margin, marketing cost, marketing profit, corn farmer's share, marketing efficiency of maize in various channel in Kalampangan village. The results showed that: (1) marketing of corn in Kalampangan village there are two kinds of channels, where channel I involves four institutions namely: farmers, merchants village, retailers, and consumers. While channel II involves two institutions only, namely, farmers as traders and consumers. Maize's marketing functions are: sales function, purchasing function, storage function, transport function and facility function. (2) From calcution result at Marketing Channel I, total marketing margin of maize in Kalampangan Villge is Rp. 3.860,-/kg, total cost of corn marketing is Rp. 310,-/kg, total profit of corn marketing is Rp. 3.550,-/kg and the result obtained by corn farmer are 58,04%. From calculating result at Marketing Channel II, total margin of maize in Kalampangan Village is Rp. 2.160,-/kg, total cost of corn marketing is Rp. 310,-/kg, total profit of corn marketing is Rp. 1.850,-/kg and the result obtained by corn farmer are 71,20%. (3) marketing efficiency at Marketing Channel I equal to 41.96%, and on Marketing Channel II is 28,80%. Marketing efficiency value in Channel I is lower than marketing efficiency II, it is considered more efficient marketing Channel II.